Air monitoring of polychlorinated biphenyls, polybrominated diphenyl ethers and organochlorine pesticides in West Antarctica during 2011–2017: Concentrations, temporal trends and potential sources. (June 2019) - Hao, Yanfen; Li, Yingming; Han, Xu; Wang, Thanh; Yang, Ruiqiang; Wang, Pu; Xiao, Ke; Li, Wenjuan; Lu, Huili; Fu, Jianjie; Wang, Yawei; Shi, Jianbo; et al.
Abstract: Annual air samples were collected at various sites in the Fildes Peninsula, West Antarctica from December 2010 to January 2018 using XAD-2 resin passive air samplers to investigate concentrations, temporal trends and potential sources of persistent organic pollutants (POPs) in Antarctic air. Relatively low concentrations of polychlorinated biphenyls (PCBs) (Σ19 PCBs: 1.5–29.7 pg/m 3 ), polybrominated diphenyl ethers (PBDEs) (Σ12 PBDEs: 0.2–2.9 pg/m 3 ) and organochlorine pesticides (OCPs) (Σ13 OCPs: 101–278 pg/m 3 ) were found in the atmosphere of West Antarctica. PCB-11, BDE-47 and hexachlorobenzene (HCB) were the predominant compounds in the atmosphere. The concentrations of PCBs, HCHs, DDTs and endosulfans were found to show decreasing temporal trends, whereas uniform temporal trends were observed for HCB. The atmospheric half-life values for PCBs, HCHs, DDTs and endosulfans in Antarctic air were estimated for the first time, using regressions of the natural logarithm of the concentrations versus the number of years, obtaining the values of 2.0, 2.0, 2.4 and 1.2 year, respectively. An increasing ratio of α -HCH/ γ -HCH indicated long residence time for α -HCH and possible transformation of γ -HCH to α -HCH in the atmosphere. The ratios of p, p'-DDT/p, p'-DDE were mostly lower than unity in this study, which could be attributed to aged sources. It was found that long-range atmospheric transport was still considered to be the main contributing factor to the atmospheric levels of the POPs in West Antarctica whereas the contribution of human activities at the Chinese Great Wall Station was minor. The results of this study give a view on the most recent temporal trends and provide new insights regarding the occurrence of various POPs in the Antarctic atmosphere. Graphical abstract: Image 1 Highlights: Atmospheric temporal trends of POPs were investigated in West Antarctica. PCBs, HCHs, DDTs and endosulfans were found in decreasing temporal trends. Uniform temporal trend was observed for HCB in the Antarctic air. DDTs in the Antarctic air were attributed to aged source. Half-life values of POPs were estimated for the first time in the Antarctic air.